A case of entecavir resistance which is developed after complete viral suppression during entecavir treatment for nucleoside-naive chronic hepatitis B - Doğan, Ümit Bilge; Öztürk, Agah Bahadır; Akın, Mustafa Salih; Yalaki, Serkan; Sayan, Murat (Turkish Journal of Gastroenterology, 2014)
Abstract Entecavir (ETV) is a potent nucleoside analogue against hepatitis B virus (HBV), and the emergence of drug resistance is rare in nucleoside-naive patients because development of ETV resistance (ETVr) requires at least three amino acid substitutions in HBV reverse transcriptase. We observed a case of genotypic ETVr with viral and biochemical breakthrough during ETV treatment of nucleoside-naive patients with chronic hepatitis B (CHB). A 57-years-old HBeAg-positive man received ETV 0.5 mg/day for 145 weeks. HBV DNA was 7.7 log10 copies/ ml at baseline, decreased to below 2 at week 48, declined to a nadir of 0 (negative) at week 72, and rebounded to 2.2 log10 copies/ ml at week 90 and remained this level until 109 weeks and increased to 6.8 log10 copies/ ml at week 145. Alanine aminotransferase (ALT) level increased to 440 IU/ L at week 145. The ETVr-related substitution (rtS202P) and lamivudine resistance-related substitutions (rtL180M + rtM204V) were detected by DNA sequencing analysis at week 145. The patient discontinued ETV therapy at week 145, and then received 245 mg of tenofovir disoproxil fumarate (TDF). Afterwards, HBV DNA level dropped to below 2.6 log10 copies/ml and ALT level was normalized after 19 weeks of TDF dosing. The three substitutions associated with ETV and lamivudine resistance developed after complete viral suppression in a nucleoside-naive CHB patient during ETV treatment. In spite of the extremely rare chance of viral mutation during ETV treatment, nucleoside-naive patients should be carefully monitored for resistance even if complete suppression is present.